2018
DOI: 10.1073/pnas.1800298115
|View full text |Cite
|
Sign up to set email alerts
|

Additive-free carbon nanotube dispersions, pastes, gels, and doughs in cresols

Abstract: Cresols are a group of naturally occurring and massively produced methylphenols with broad use in the chemical industry. Here, we report that -cresol and its liquid mixtures with other isomers are surprisingly good solvents for processing carbon nanotubes. They can disperse carbon nanotubes of various types at unprecedentedly high concentrations of tens of weight percent, without the need for any dispersing agent or additive. Cresols interact with carbon nanotubes by charge transfer through the phenolic hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Previous studies have shown that GO and carbon nanotubes’ dispersions of different concentrations can be divided into four states. [ 29,52 ] In our experiment, increasing GO/G concentrations results in a continuous transition between four states, from a dilute dispersion (<10 mg mL −1 ) to a thick paste (10–50 mg mL −1 ), a free‐standing gel (50–100 mg mL −1 ), and eventually, a kneadable, playdough‐like material (>100 mg mL −1 ). These four states were further transformed into 1D graphene fibers, 2D graphene films, or 3D graphene doughs using various material‐processing techniques (Figure S25, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that GO and carbon nanotubes’ dispersions of different concentrations can be divided into four states. [ 29,52 ] In our experiment, increasing GO/G concentrations results in a continuous transition between four states, from a dilute dispersion (<10 mg mL −1 ) to a thick paste (10–50 mg mL −1 ), a free‐standing gel (50–100 mg mL −1 ), and eventually, a kneadable, playdough‐like material (>100 mg mL −1 ). These four states were further transformed into 1D graphene fibers, 2D graphene films, or 3D graphene doughs using various material‐processing techniques (Figure S25, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The m-cresol is known to dissolve well highly conjugated polymer such as conducting polymer through second doping [23]. In the same way, the m-cresol interacts with the CNT by charge-transfer through the phenolic hydroxyl proton [13]. By this mechanism, m-cresol initially disperses the nanotubes well at high concentrations to produce a thick CNT paste.…”
Section: Physical and Thermal Propertiesmentioning
confidence: 99%
“…A macronization of nanoparticles, such as the CNT particles, can generally be achieved by the solvent-based strategies for dispersion and processing of the particles. However, some types of solvents for the direct dilution such as 1,2-dichrolobenzene [11], dimethylformamide (DMF) [12] and N-methyl-2-pyrrolidone (NMP) [12] can disperse the nanotubes less than 0.02 wt %, indicating extensive solvents treating and uneconomical efforts in the process of the CNT macronization [13]. Most of the studies have used single-walled CNTs (SWCNTs) for their application in the electronic device [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of experiments done with most common solvents to get stable dispersions of CNTs (Fukushima et al, 2003;Bergin et al, 2009;Davis et al, 2009); however, generally the most common solvents used, such as N-methyl-2-pyrrolidone, dimethylformamide, and 1,2-dichrolobenzene, can disperse only CNTs with specific size and dimension at low concentrations. Recently, Chiou et al (2018) dispersed carbon nanotube powders in m-cresol at very high concentrations giving them a doughlike consistency. However, m-cresol is highly volatile, and the processing requires a controlled environment.…”
Section: Introductionmentioning
confidence: 99%